Minimally Invasive Technique for PMMA Augmentation of Fenestrated Screws - Jan-Helge Klingler; Christoph Scholz; Evangelos Kogias; Ronen Sircar; Marie T. Krüger; Florian Volz; Christian Scheiwe; Ulrich Hubbe (The Scientific World Journal)
Purpose. To describe the minimally invasive technique for cement augmentation of cannulated and fenestrated screws using an injection cannula as well as to report its safety and efficacy. Methods. A total of 157 cannulated and fenestrated pedicle screws had been cement-augmented during minimally invasive posterior screw-rod spondylodesis in 35 patients from January to December 2012. Retrospective evaluation of cement extravasation and screw loosening was carried out in postoperative plain radiographs and thin-sliced triplanar computed tomography scans. Results. Twenty-seven, largely prevertebral cement extravasations were detected in 157 screws (17.2%). None of the cement extravasations was causing a clinical sequela like a new neurological deficit. One screw loosening was noted (0.6%) after a mean follow-up of 12.8 months. We observed no cementation-associated complication like pulmonary embolism or hemodynamic insufficiency. Conclusions. The presented minimally invasive cement augmentation technique using an injection cannula facilitates convenient and safe cement delivery through polyaxial cannulated and fenestrated screws during minimally invasive screw-rod spondylodesis. Nevertheless, the optimal injection technique and design of fenestrated screws have yet to be identified. This trial is registered with German Clinical Trials DRKS00006726.